Case report of the broad spectrum of late complications in an adult patient with univentricular physiology palliated by the Fontan circulation. Issue 2 (16th February 2022) - Nederend, Marieke; Egorova, Anastasia D; Vliegen, Hubert W; Roest, Arno A W; Ruijter, Bastian N; Korteweg, Tijmen; Ninaber, Maarten K; Zeppenfeld, Katja; Hazekamp, Mark G; Kiès, Philippine; Jongbloed, Monique R M
Abstract: Background: At the most severe end of the spectrum of congenital heart disease are patients with an univentricular physiology. They comprise a heterogeneous group of congenital heart malformations that have the common characteristic that the cardiac morphology is not equipped for sustaining a biventricular circulation. Case summary: Here, we present a case of an adult patient after Fontan palliation, illustrative of the complex clinical course and the broad spectrum of complications that can be encountered during follow-up, highlighting the need for a multidisciplinary approach in the clinical care for these patients. Discussion: During the surgical Fontan procedure, the inferior vena cava is connected to the pulmonary circulation, after prior connection of the superior vena cava to the pulmonary arterial circulation. The resulting cavopulmonary connection, thus lacking a subpulmonic ventricle, provides non-pulsatile passive flow of oxygen-poor blood from the systemic venous circulation into the lungs, and the functional monoventricle pumps the oxygen-rich pulmonary venous return blood into the aorta. With an operative mortality of <5% and current 30-year survival rates up to 85%, the adult population of patients with a Fontan circulation is growing. This increase in survival is, however, inevitably accompanied by long-term complications affecting multiple organ systems, resulting in decline in cardiovascular performance. Conclusion: For optimal treatment, the evaluation in a multidisciplinary team is mandatory, using the specific expertise of the team members to timely detect and address late complications and to support quality of life.